The potential for autonomic neuromodulation to reduce perioperative complications and pain: a systematic review and meta-analysis. (January 2022) - Patel, Amour B.U.; Weber, Valentin; Gourine, Alexander V.; Ackland, Gareth L.
Abstract: Background: Autonomic dysfunction promotes organ injury after major surgery through numerous pathological mechanisms. Vagal withdrawal is a key feature of autonomic dysfunction, and it may increase the severity of pain. We systematically evaluated studies that examined whether vagal neuromodulation can reduce perioperative complications and pain. Methods: Two independent reviewers searched PubMed, EMBASE, and the Cochrane Register of Controlled Clinical Trials for studies of vagal neuromodulation in humans. Risk of bias was assessed; I 2 index quantified heterogeneity. Primary outcomes were organ dysfunction (assessed by measures of cognition, cardiovascular function, and inflammation) and pain. Secondary outcomes were autonomic measures. Standardised mean difference (SMD) using the inverse variance random-effects model with 95% confidence interval (CI) summarised effect sizes for continuous outcomes. Results: From 1258 records, 166 full-text articles were retrieved, of which 31 studies involving patients ( n =721) or volunteers ( n =679) met the inclusion criteria. Six studies involved interventional cardiology or surgical patients. Indirect stimulation modalities (auricular [ n =23] or cervical transcutaneous [ n =5]) were most common. Vagal neuromodulation reduced pain ( n =10 studies; SMD=2.29 [95% CI, 1.08–3.50]; P =0.0002; I 2 =97%) and inflammation ( n =6 studies; SMD=1.31 [0.45–2.18]; P =0.003; I 2 =91%), and improved cognition ( n =11 studies; SMD=1.74 [0.96–2.52]; P <0.0001; I 2 =94%) and cardiovascular function ( n =6 studies; SMD=3.28 [1.96–4.59]; P <0.00001; I 2 =96%). Five of six studies demonstrated autonomic changes after vagal neuromodulation by measuring heart rate variability, muscle sympathetic nerve activity, or both. Conclusions: Indirect vagal neuromodulation improves physiological measures associated with limiting organ dysfunction, although studies are of low quality, are susceptible to bias and lack specific focus on perioperative patients.